Association between Circulating Growth Differentiation Factor 15 and Cirrhotic Primary Biliary Cholangitis. (29th October 2020) - Li, Zhanyi; Liu, Yu; Li, Xiangyong; Wu, Yuankai; Yang, Fangji; Mo, Qiwan; Chong, Yutian
Abstract : Primary biliary cholangitis (PBC) is a common condition that usually shows a progressive course towards cirrhosis without adequate treatment. Growth differentiation factor 15 (GDF15) plays multiple roles in various pathological conditions. The overall role of circulating GDF15 in cirrhotic PBC requires further investigation. Twenty patients with cirrhotic PBC, 26 with non-cirrhotic PBC, and 10 healthy subjects were enrolled between 2014 and 2018, and the serum levels of GDF15 were measured via enzyme immunoassay. The correlations between serum GDF15, weight, biochemical parameters, and the prognosis were analysed. Serum levels of GDF15 were significantly higher in cirrhotic PBC patients than in non-cirrhotic PBC patients or healthy controls (p = 0.009 and p < 0.001, respectively). The circulating GDF15 levels strongly correlated with weight changes (r = − 0.541, p = 0.0138 ), albumin (r = − 0.775, p < 0.0001 ), direct bilirubin (r = − 0.786, p < 0.0001 ), total bile acids (r = 0.585, p = 0.007 ), and C-reactive protein (r = 0.718, p = 0.0005 ). Moreover, circulating GDF15 levels strongly correlated with the Mayo risk score (r = 0.685, p = 0.0009 ) and Model for End-stage Liver Disease score (r = 0.687, p = 0.0008 ). Determined by the area under the receiver operating characteristic curves, the overall diagnostic accuracies of GDF15 were as follows: cirrhosis = 0.725 (>3646.55 pg/mL, sensitivity: 70.0%, specificity: 69.2%), decompensated   cirrhosis = 0.956 (>4073.30 pg/mL, sensitivity: 84.62%, specificity: 100%), and cirrhotic biochemical non-responders = 0.835 (>3479.20 pg/mL, sensitivity: 71.43%, specificity: 92.31%). GDF15 may be a useful and integrated biochemical marker to evaluate not only the disease severity and prognosis but also the nutrition and response to treatment of cirrhotic PBC patients, and its overall performance is satisfactory. Therapy targeting GDF15 is likely to benefit cirrhotic PBC patients and is worth further research.